Thoracic endometriosis with catamenial haemoptysis and pneumothorax: Computed tomography findings and long-term follow-up after danazol treatment - Thitiporn Suwatanapongched (2018)
© 2015, Singapore Medical Association. All rights reserved. Thoracic endometriosis (TE) is an uncommon disorder affecting women of childbearing age. We herein report clinical and thin-section computed tomography (CT) findings of two cases, in which one woman presented with catamenial haemoptysis (CH) alone and another woman presented with bilateral catamenial pneumothoraces (CP) coinciding with CH, a rare manifestation of TE. The dynamic changes demonstrated on thin-section chest CT performed during and after menses led to accurate localisation and presumptive diagnosis of TE in both patients. Following danazol treatment, the patient with CH alone had a complete cure, while the patient with CP and CH had an incomplete cure and required long-term danazol treatment. We discuss the role of imaging studies in TE, with an emphasis on the appropriate timing and scanning technique of chest CT in women presenting with CH, potential mechanisms, treatment and patient outcomes.